2014
DOI: 10.1038/ejhg.2014.95
|View full text |Cite
|
Sign up to set email alerts
|

Baraitser–Winter cerebrofrontofacial syndrome: delineation of the spectrum in 42 cases

Abstract: Baraitser-Winter, Fryns-Aftimos and cerebrofrontofacial syndrome types 1 and 3 have recently been associated with heterozygous gain-of-function mutations in one of the two ubiquitous cytoplasmic actin-encoding genes ACTB and ACTG1 that encode b-and c-actins. We present detailed phenotypic descriptions and neuroimaging on 36 patients analyzed by our group and six cases from the literature with a molecularly proven actinopathy (9 ACTG1 and 33 ACTB). The major clinical anomalies are striking dysmorphic facial fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
180
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(192 citation statements)
references
References 48 publications
7
180
0
5
Order By: Relevance
“…Many patients with ACTB and ACTG1 mutations have pachygyria with an anteriorto-posterior severity gradient, similar to that observed in males with DCX mutations [Rivière et al, 2012a;Verloes et al, 2015].…”
Section: Clinical Featuresmentioning
confidence: 83%
See 1 more Smart Citation
“…Many patients with ACTB and ACTG1 mutations have pachygyria with an anteriorto-posterior severity gradient, similar to that observed in males with DCX mutations [Rivière et al, 2012a;Verloes et al, 2015].…”
Section: Clinical Featuresmentioning
confidence: 83%
“…Mutations in the ACTB and ACTG1 genes are associated with Baraitser-Winter cerebrofrontofacial syndrome which is characterized by the combination of hypertelorism, a broad nose with a large tip and prominent root, congenital nonmyopathic ptosis, ridged metopic suture, arched eyebrows, iris or retinal coloboma, sensorineural deafness, shoulder girdle muscle bulk, and progressive joint stiffness [Rivière et al, 2012a;Di Donato et al, 2014;Verloes et al, 2015]. Many patients with ACTB and ACTG1 mutations have pachygyria with an anteriorto-posterior severity gradient, similar to that observed in males with DCX mutations [Rivière et al, 2012a;Verloes et al, 2015].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Additionally, patient 2 showed features that are not typically found in persons with ACTB mutations, such as ventricular arrhythmia with prenatal debut and thrombocytopenia. Individuals with ACTB mutations have been reported with a broad phenotypic variability [Verloes et al, 2015] and, in some cases, described as distinct clinical entities [Johnston et al, 2013]. Verloes et al [2015] studied 36 patients with a molecularly proven actinopathy and described 6 additional cases from the literature (33 ACTB and 9 ACTG1).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with ACTB mutations have been reported with a broad phenotypic variability [Verloes et al, 2015] and, in some cases, described as distinct clinical entities [Johnston et al, 2013]. Verloes et al [2015] studied 36 patients with a molecularly proven actinopathy and described 6 additional cases from the literature (33 ACTB and 9 ACTG1). They suggested that there could be an important mutation-specific variability in the phenotype of actinopathies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation